World agricultural trade : building a consensus - Miner, William M.; Hathaway, Dale E. (Halifax, Nova Scotia : The Institute for Research on Public Policy, 1988)
This book, a joint publication of the Institute of Research on Public Policy and the Institute for International Economics, contains a detailed consensus of policy conclusions and recommendations reached by this group in Ottawa on April 21 and 22, 1988
Includes bibliographical references.
osc 28/01/2019
Loans
Keywords: Agricultural Economics; Produce trade